Manajemen sarana prasarana dalam rangka implementasi kurikulum 2013 di SMA Negeri 5 Mataram Nusa Tenggara Barat tahun ajaran 2013/ 2014 - Ita Faramita Sari; Supriyoko Supriyoko (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
The purpose of this study was to describe about on the management of infrastructure facilities in the implementation of the curriculum in 2013 from planning, procurement, distribution, use, and maintenance, inventory and pengahpusan, and completeness of the existing infrastructure as well as the constraints that may affect the management of infrastructures in order curriculum implementation in 2013. This study includes a qualitative descriptive study. The research location is housed in SMA 5 Mataram. Data collection was done by conducting observations, interviews, and documentation. Data analysis is done by giving meaning to the data collected, and from these data in Narrate and conclusions drawn. The results of this study illustrate the management process management infrastructure, as well as the completeness and constraints that affect the infrastructure. The results of these studies that the management of the infrastructure in SMAN 5 Mataram is in conformity with the technical management, including planning, procurement, distribution, use, and maintenance, inventory, and pengahpusan. 1) the work done to improve the management of infrastructure in 2013, namely the implementation of the curriculum, increasing teacher training diligently and frequently follow and training, students are more disciplined, supportive classroom situation. 2) infrastructure in SMA 5 Mataram influential in the learning curriculum implementation in 2013 are classrooms, administration, library room, counseling, and prayer room. 3) infrastructure constraints are often delays in the distribution of textbooks still be overcome.